a=(3√2 - 2√3 ) (3√2+2√3 ) - √72-(3-√2 )2
Răspunsuri la întrebare
Răspuns de
0
A=(3√2 - 2√3 ) (3√2+2√3 ) - √72-(3-√2 )2A=(3√2)²-(2√3)²-3√2-(3-√2)2
A=√18²-√12²-3√2-(6-2√2)
A=18-12-3√2-6+2√2
A=6-3√2+2√2-6
A=-0-1√2
A=-1√2
A=√18²-√12²-3√2-(6-2√2)
A=18-12-3√2-6+2√2
A=6-3√2+2√2-6
A=-0-1√2
A=-1√2
Alte întrebări interesante
Religie,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Geografie,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
10 ani în urmă
Limba română,
10 ani în urmă